Equality of internal angles and vertex points in conformal hyperbolic triangles - TOKEŞER, Ümit; ALSAN, Ömer (Cumhuriyet University, 2020)
In this article, by using the conformal structure in Euclidean space, the conformal structures in hyperbolic space and the equality of the internal angles and vertex points of conformal triangles in hyperbolic space are given. Especially in these special conformal triangles, the conformal hyperbolic equilateral triangle and the conformal hyperbolic isosceles triangle, the internal angles and vertices are shown.
Keywords: Matematik; Mathematical Sciences; Conformal hyperbolic triangle; Conformal hyperbolic isosceles triangle; Conformal hyperbolic equilateral triangle